Constructing RNA Viruses for Long-Term Transcriptional Gene Silencing. Issue 1 (January 2019) - Baltusnikas, Juozas; Satkauskas, Saulius; Lundstrom, Kenneth
Abstract : Recent discoveries have shown that self-replicating RNA viruses can produce small RNAs (sRNAs) in host cells. Given their potential to be modified to generate short-term transgene expression without integrating viral sequences into the host genome, these viruses could be used as safe delivery vehicles for sRNAs to induce long-term transcriptional gene silencing (TGS). This might open new avenues for therapeutic approaches, where a single administration would safely induce long-term therapeutic effects for various diseases. Here, we introduce and discuss the possible use of cytoplasmic alphaviruses, flaviviruses, Sendai virus (SeV), and nucleoplasmic Influenza A (IAV) and Borna disease (BoDV) viruses to induce long-term TGS. Highlights: Self-replicating RNA viruses can produce sRNAs. Self-replicating RNA viruses may be used to induce sRNA-mediated long-term TGS. The ability to induce long-term TGS might lead to long-term therapy for various diseases after a single administration. Developing self-replicating, self-destructive RNA viruses that can induce long-term therapeutic effects is inherently a safer approach than others that require continuous drug administration or continuous synthesis of therapeutic biomolecules.